2017
DOI: 10.1007/s10456-017-9561-x
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 suppression of hem- and lymph-angiogenesis in inflamed corneas through MMP13

Abstract: Though not present in the normal adult cornea, both hem- and lymph-angiogenesis can be induced in this tissue after an inflammatory, infectious, or traumatic insult. We previously showed that the chemokine CXCL10 plays a key role in eradicating invading Candida (C.) albicans in C57BL6 mouse corneas. However, even after the clearance of pathogens, infection-induced inflammation and angiogenesis continue to progress in the cornea. The aim of this study is define the role of CXCL10 as a major angiostatic factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…3c). The different cell types can be identified with specific cell markers by immunostaining whole-mount preparations [101] of the aortic cultures (Fig. 3d–g).…”
Section: Aortic Ring Assaymentioning
confidence: 99%
“…3c). The different cell types can be identified with specific cell markers by immunostaining whole-mount preparations [101] of the aortic cultures (Fig. 3d–g).…”
Section: Aortic Ring Assaymentioning
confidence: 99%
“…These results may indicate that the angiostatic effect of the CXCR3 ligands is a CXCR3-dependent phenomenon, at least when chemokines are exogenously added. Moreover, in a murine model of Candida albicans uveitis, neutralization of CXCR3 increased angiogenesis in the cornea, indicating that murine CXCR3 in this model provides a negative feedback on vessel formation ( 181 ). A similar observation was made in vitro in cocultures of human pericytes and endothelial cells.…”
Section: Unprecedented Versatility Of Ifn-inducible Cxcr3 Ligands As mentioning
confidence: 99%
“…In such a context, a very recent study has demonstrated that levels of CXCL10 and CXCL11, two C-X-C chemokines exerting angiostatic effects through their receptor CXCR3-B [49], are strongly increased in the circulation of SSc patients from the earliest disease stages, and may represent good biomarkers of vascular damage progression [50]. Interestingly, both CXCL10 and CXCL11 have been reported to potently inhibit the lymphangiogenic process [51,52], making them very attractive candidates as possible mediators of SSc-related, disturbed lymphangiogenesis, and are worthy of future investigation.…”
Section: Discussionmentioning
confidence: 99%